2016
DOI: 10.1002/micr.30080
|View full text |Cite
|
Sign up to set email alerts
|

Internal mammary artery perforator propeller flap for contralateral mastectomy defect: A case report

Abstract: The internal mammary artery perforator (IMAP) flap can be used as either loco-regional or free flap, and provides thin flexible coverage for defects of the chest wall and cervical regions. In this report, we present a bilateral mastectomy case in which the left mastectomy defect was closed with an IMAP propeller flap harvested from the right breast. Our patient with a history of left breast conservation therapy was diagnosed invasive ductal carcinoma in her left breast 14 years later. On physical examination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Additionally, as published previously (Dolen et al, 2016), the anatomy of the second and third IMAP flaps ensures the acquisition of a sufficient flap volume. When we separated the vascular tip, we did not pursue skeletal treatment; instead, based on preoperative vascular imaging, we separated it to the perivascular area with an overlay of 0.5 to 0.8 cm of fatty tissue to avoid damage and excessive traction of the tip.…”
Section: Casementioning
confidence: 80%
See 2 more Smart Citations
“…Additionally, as published previously (Dolen et al, 2016), the anatomy of the second and third IMAP flaps ensures the acquisition of a sufficient flap volume. When we separated the vascular tip, we did not pursue skeletal treatment; instead, based on preoperative vascular imaging, we separated it to the perivascular area with an overlay of 0.5 to 0.8 cm of fatty tissue to avoid damage and excessive traction of the tip.…”
Section: Casementioning
confidence: 80%
“…Most previous reports (Dolen et al, 2016; Novo‐Torres et al, 2015; Schoeller et al, 2001) have indicated that hypertrophic breasts of women who have undergone mastectomy are suitable for contralateral breast reconstruction. Additionally, He et al (2020) demonstrated that the lower part of the breast was the best choice for contralateral breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 reviews the existing studies focused on ipsilateral IMAP flaps. 4,[9][10][11][12][13][14][15][16] The maximum dimensions of flaps (in centimeters), the maximum length (in centimeters), and the maximum corresponding area in different case series published on deltopectoral IMAP. There was a total of 22 cases in which the IMAP flap was used.…”
Section: Resultsmentioning
confidence: 99%
“…The flap is especially beneficial in women with large breasts with a flap size reported of up to 26 cm × 11 cm, which can be saved from a breast undergoing a prophylactic mastectomy. 19 Unfortunately, lack of excess skin tissue in women with smaller breasts may necessitate the need for backgrafting of the donor site. The poor cosmesis of this flap lends it as a backup solution for coverage as the donor nipple can end in an odd location and because the pivot point of the flap can be bulky over the sternum.…”
Section: Introductionmentioning
confidence: 99%